Biology and Control of the Strawberry Aphid, Chaetosiphon fragaefolli (Cockerell) (Homoptera: Aphididae) in Florida - Silvia I. Rondon; Daniel J. Cantliffe (EDIS)
The strawberry (Fragaria x ananassa Duchesne) hosts a wide variety of aphid species. Most of these species have an ample variety of alternate hosts that include strawberries. The true strawberry aphid, Chaetosiphon fragaefolli (Cockerell) (Fig. 1), is considered an important pest of wild and cultivated strawberries worldwide. This aphid species is a vector of strawberry viruses such as cytorhabdovirus, one of the most dangerous viruses affecting strawberry (Krczal, 1979) (Fig. 2). Our ability to recognize this pest and the damage it causes is important in determining successful control methods. This document is HS1009, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2005.